World Experience and Features of Tax Revenue Formation of Local Budgets - MEDYNSKA, T. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
The article examines the world experience in the formation of tax revenues of local budgets. Based on the results of World Bank research, it was found that the highest level of financial autonomy is characterized by the municipalities of those countries whose local budget revenues are dominated by tax revenues. Scandinavian countries (Sweden, Iceland, Denmark, Finland) are traditionally characterized by the highest indicators of redistribution of tax revenues through the local level of management. During the analysis of the structure of tax revenues to budgets at the local level in the OECD countries, the presence of two differentiated models of taxation at the level of municipalities was revealed: focused on taxation of income and income (Sweden, Luxembourg, Finland, Denmark, Norway, Latvia, Switzerland, Iceland); focused on property taxation (Great Britain, Canada, Greece, Ireland, Lithuania, Estonia). The factors of the formation of tax revenues of municipal budgets are considered in view of these two models. As a result of researching trends in the development of the taxation system in foreign countries and comparing them with Ukrainian realities, we determined that in Ukraine, unlike many developed countries, it was possible to avoid excessive dependence of local self-government bodies on the payment of certain taxes to local budgets. The conducted analysis made it possible to identify the factors influencing property taxation systems in different countries, which determine their formation, in particular: the difference in the structure of the economy and the impact of its changes, the behavioral reactions of economic subjects and the existing traditions of property ownership in different countries, the peculiarities of the development of the real estate market in different countries, etc. For Ukraine, these issues are relevant, first of all, in the context of changing the structure of the economy as a country on the territory of which hostilities continue (which is accompanied by different trends in different territories and, in fact, a complete change in the socio-economic situation), which will have a direct impact on the formation of revenues of community budgets in the post-war period.